Gastrectomy-induced alterations in gut microbiota linked to changes in oral and gastric microbiota - Komori, Eri; Kato-Kogoe, Nahoko; Imai, Yoshiro; Sakaguchi, Shoichi; Taniguchi, Kohei; Omori, Michi; Ohmichi, Mayu; Hamada, Wataru; Nakamura, Shota; Nakano, Takashi; Lee, Sang-Woong; Ueno, Takaaki (Frontiers in Microbiology, 2025)
IntroductionGastrectomy serves as a primary treatment for gastric cancer, a leading global malignancy, and affects significant physiological and anatomical changes in the digestive tract. Recent studies highlight the critical role of gastrointestinal microbiota in postoperative health following digestive tract surgeries, including gastrectomy. These alterations possibly impact the gut microbiota and affect patient health by influencing the bacterial environment in the gastrointestinal tract. However, the relationships between the gastrointestinal tract and the oral, gastric, and gut microbiota after gastrectomy are not clear. In this study, we aimed to characterize alterations in the gut microbiota due to gastrectomy and evaluate whether these alterations are associated with the oral and gastric microbiota.MethodsSaliva, gastric fluid, and stool samples were collected from patients diagnosed with primary gastric cancer who underwent gastrectomy at two time points, before and 6 months after gastrectomy. Next, 16S rRNA metagenomic analysis was performed. Diversity and linear discriminant analysis effect size (LEfSe) analyses of each microbiota were conducted before and after gastrectomy to compare alterations in the gut, oral, and gastric microbiota.ResultsThe diversity of gut microbiota increased after gastrectomy compared to that before gastrectomy (Shannon index, p = 0.044), with LEfSe analysis showing increased abundance of Rothia and Lactobacillus in the gut microbiota. Additionally, the proportion of participants with Rothia in their gut microbiota increased, and this genus was present in the oral and gastric microbiota of almost all participants. Furthermore, a significant rise in Lactobacillus was observed in the gut, oral, and gastric microbiota of paired participants.DiscussionWe characterized gut microbiota alterations caused by gastrectomy and demonstrated their relationship with changes in oral and gastric microbiota, thereby elucidating interactions between the gastrointestinal tract microbiota in response to changes in the gastric environment.